Adjacent segment disease induced by spinal tophus: a case report - Wang, Chenglong; Liu, Hongjun; Gong, Shuangquan; Ye, Yu; Cui, Liqiang; Liu, Dengshang; Li, Sen; Xie, Shiming (Frontiers in Surgery, 2025)
Tophus, a hallmark feature of chronic gout, typically develops in the joints of the extremities, skin, and mucosal tissues. Although several case reports have described spinal tophus deposition leading to spinal stenosis and radiculopathy, documented cases of lumbar adjacent segment disease (ASD) caused by monosodium urate crystal (MUC) deposition remain exceedingly rare. Here, we report the case of a 56-year-old male who underwent L4-S1 lumbar fusion surgery two years prior for L4-S1 disc herniation with radiculopathy. The patient presented with recurrent low back pain, radiculopathy, and systemic tophus involvement. Magnetic resonance imaging (MRI) T2-weighted sequences revealed a hypointense signal at the posterior margin of the L3 vertebral body, while computed tomography (CT) demonstrated a hyperdense lesion. These radiographic findings suggested dural sac compression and spinal stenosis, though the definitive etiology warranted further evaluation. Surgical intervention involved excision of the L3 posterior lesion and extension of the fusion construct from L4-S1 to L2-S1 based on the existing L4-S1 instrumentation for spinal stabilization. Histopathological examination confirmed extensive MUC deposition. This report details the clinical presentation, imaging characteristics, pathological findings, surgical management, and potential pathogenic mechanisms underlying this rare complication.